The Effect Of Liquidity, Solvency, Profitability and Activity On Financial Performance AT PT. Adi Sarana Armada Tbk On The IDX - Mulia Sari; Nasution, Nina Andriany (International Forum of Researchers and Lecturers, 2024)
This research is motivated by a decrease in the Liquidity Ratio in cash and cash equivalents due to an increase in investment acquisition and purchase of fixed assets which will cause depreciation expenses in the coming years to be greater which will directly reduce the company's profit. The Solvency Ratio has increased due to an increase in debt which will directly increase interest expenses, so it must be covered from operating profit. The Profitability Ratio has decreased in current year profit because the increasing amount of expenses will reduce net profit. The Activity Ratio has decreased inventory turnover due to decreased sales which has resulted in an increase in the amount of inventory. The purpose of this study is to determine the effect of Liquidity, Solvency, Profitability and Activity on Financial Performance at PT. Adi Sarana Armada Tbk. which is listed on the Indonesia Stock Exchange (IDX). The method used in this study is a quantitative descriptive method, the data in this study uses secondary data. Based on the results of the study, it shows that Liquidity ratio using Current Ratio has a partial positive effect on Financial Performance with Good criteria, this shows the company's ability to pay short-term obligations. Solvency ratio using Debt To Equity Ratio does not have a partial effect on Financial Performance with Poor criteria, this shows the company's inability to meet long-term obligations because risk assessment is ineffective, resulting in a greater risk of loss. Profitability ratio using Return On Asset does not have a partial effect on Financial Performance with Poor criteria, this shows that it is inefficient in using its assets to generate profits and ineffectiveness in accounts receivable turnover so that the small capital invested. Activity ratio using Total Asset Turn Over has a partial positive effect on Financial Performance with Very Good criteria, this shows the company's ability to utilize its assets to generate income.